Seasonal variation in gastrointestinal helminth infection of beef cows and effect of Ivermecthrin at different intervals - Maia, Antonio Augusto Mendes; Guimarães, Marcos Pezzi (Pesquisa Agropecuaria Brasileira, 2014)
Fifty-five nellore cows with gastrointestinal nematode infections were divided into five groups of eleven animals each; one group was taken as the control, and to the ether four groups were given 200 mcg/kgbw of Ivermectin at intervals of 60, 75, 90 and 120 days throughout the year. The treatments one, two and three had some effect in the subclinic nematode gastrointestinal infections, while the treatment number 4 had no effect at all. Cooperia was the most frequent infective larvae found in the coprocultures, followed by Haemonchus, Oesophagostomum and Trichostrongylus larvae respectively. There were no differences in the worm burden between the dry and wet seasons.